Adsorption Kinetic Modeling of Cyanide by Activated Carbon from Solution by Using of Kinetic Models and Adaptive Neuro-fuzzy Inference System - BEHNAMFARD*, A.; SALARI RAD, M.M. (Asian Journal of Chemistry, 2024)
Adsorption kinetics of cyanide on coconut shell activated carbon were determined from batch tests. The kinetic data were fitted to pseudo-first-order and pseudo-second-order kinetic models and was found to follow closely the pseudo-second-order kinetic model. Remaining cyanide concentration in wastewater at several time after addition coconut shell activated carbon are modeled by adaptive neuro-fuzzy inference system (ANFIS) at different initial cyanide concentration. The results obtained in this work indicate that ANFIS is an effective method for prediction of remaining cyanide concentration in solution and have better accuracy and simplicity compared with results obtained from the applicablekinetic model.